A critical review of microextraction by packed sorbent as a sample preparation approach in drug bioanalysis. (June 2013) - Alves, Gilberto; Rodrigues, Márcio; Fortuna, Ana; Falcão, Amílcar; Queiroz, João
Sample preparation is widely accepted as the most labor-intensive and error-prone part of the bioanalytical process. The recent advances in this field have been focused on the miniaturization and integration of sample preparation online with analytical instrumentation, in order to reduce laboratory workload and increase analytical performance. From this perspective, microextraction by packed sorbent (MEPS) has emerged in the last few years as a powerful sample preparation approach suitable to be easily automated with liquid and gas chromatographic systems applied in a variety of bioanalytical areas (pharmaceutical, clinical, toxicological, environmental and food research). This paper aims to provide an overview and a critical discussion of recent bioanalytical methods reported in literature based on MEPS, with special emphasis on those developed for the quantification of therapeutic drugs and/or metabolites in biological samples. The advantages and some limitations of MEPS, as well as its comparison with other extraction techniques, are also addressed herein.